Method of extracting solar cell parameters from derivatives of dark I–V curves - Hallam, BJ; Hamer, PG; Bonilla, RS; Wenham, SR; Wilshaw, PR (IEEE, 2017)
A method is presented to extract solar cell parameters from the derivatives of dark current-voltage curves with a three-diode model, using the monotonic properties of the current-voltage characteristic associated with each diode or resistive current. The method yields an improved accuracy of the solar cell parameters when compared with that used on the actual current-voltage curves. Despite the complexity of the three-diode model with seven fit parameters, a good accuracy can be reached using the proposed method with a relatively small computational effort. A hypothetical case is presented using various approaches to obtain the solar cell parameters, with a root-mean-square error for the logarithm of the current-voltage curve (RMS log10 I) of 4 × 10 -3 . An example fitting is then demonstrated on a multicrystalline passivated emitter rear contact solar cell, yielding RMS log10 I = 1.45 × 10 -1 .